Prevalence of celiac artery compression by median arcuate ligament in patients with splanchnic artery aneurysms/pseudoaneurysms submitted to endovascular embolization - Borges, Ana Paula (2023)
Purpose To study the association between median arcuate ligament compression (MALC) of celiac artery (CA) and splanchnic artery aneurysms/pseudoaneurysms (SAAPs) submitted to endovascular embolization. Methods Single center retrospective study of embolized SAAPs between 2010 and 2021, to evaluate the prevalence of MALC, and compare demographic data and clinical outcomes between patients with and without MALC. As a secondary objective, patient characteristics and outcomes were compared between patients with different causes of CA stenosis. Results MALC was found in 12.3% of 57 patients. SAAPs were more prevalent in the pancreaticoduodenal arcades (PDAs) in patients with MALC, compared to those without MALC (57.1% vs. 10%, P = .009). Patients with MALC had a greater proportion of aneurysms (71.4% vs. 24%, P = .020), as opposed to pseudoaneurysms. Rupture was the main indication for embolization in both groups (71.4% and 54% of patients with and without MALC, respectively). Embolization was successful in most cases (85.7% and 90%), with 5 immediate (28.6% and 6%) and 14 non-immediate (28.6% and 24%) post-procedure complications. Thirty and 90-day mortality rate were 0% in patients with MALC, and 14% and 24% in patients without MALC. Atherosclerosis was the only other cause of CA stenosis, in 3 cases. Conclusions In patients with SAAPs submitted to endovascular embolization, the prevalence of CA compression by MAL is not uncommon. The most frequent location for aneurysms in patients with MALC is in the PDAs. Endovascular management of SAAPs is very effective in patients with MALC, with low complications, even in ruptured aneurysms.